PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 031 SEMINAI PEMATANG REBA KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Efi Daliani; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated to learn science is still low yields Seminai SDN 031 with an average of 60.70. Still centered learning to teachers and students received less encouragement to develop the ability to think that they have so low learning outcomes. The purpose of this study is the application of guided inquiry learning model can improve learning outcomes students of class V SDN 031 Seminai in the subject matter of light and its properties. This research was conducted by the method of action research. The subjects were students of class V SDN 031 Seminai the number of students 23 people. Instrument research include syllabi, lesson plan, student worksheets. The data analysis using descriptive analysis. Learning outcomes analyzed increase learning outcomes, student activities and teacher activity. The results showed an increase in learning from the first cycle to the second cycle. To increase learning outcomes increased from 60.70 into 69.35 with an increase of 13.80%. Learning activities of students of the first cycle with an average of 55.25 into 73.46 in the second cycle. The activities of teachers in the first cycle increased from 60.00% to 81.25% in the second cycle. For student activity based on the results of the study an increase in activity of students in the learning process, while the teacher found increased activity in terms of guiding students in the learning process has been very good and the teachers are also no longer as the central conduit of information. Based on the results of the study it can be concluded that the application of guided inquiry learning model can improve learning outcomes students of class V SDN 031 Seminai.Keywords: Guided Inquiry Learning Model, Science Learning Outcomes